The Mapping Regional Potential to Optimize Local Resources in Sumberadi Village, Mlati Subdistrict, Sleman Regency - Widyastuti, Tita; Arsanti, Vidyana; Meliyani, Siti (Universitas Negeri Semarang, 2025)
Sleman Regency, located in the Special Region of Yogyakarta, has diverse geographical and social characteristics, making it a region with high economic potential. The regency is well known for its strong agricultural sector as well as rapid economic growth in trade and small and medium enterprises (SMEs). Sumberadi Village, located in Mlati District, Sleman Regency, possesses significant regional potential. This study was conducted to identify and map the potential of Sumberadi Village in order to optimize local resources. The methods used included Focus Group Discussions (FGDs) and field observations. The objective of this research is to identify the main potential sectors and analyze their spatial distribution. A qualitative descriptive analysis was employed. The results show that the main potentials of Sumberadi Village include the agriculture, fisheries, cattle farming sectors, and SMEs that produce emping and slondok. In contrast, trade centers and cultural arts show relatively lower potential. This study also produced the 2024 Sumberadi Village Potential Map, which illustrates the spatial distribution of these potentials and highlights the diverse concentrations of economic and social activities across the village. The distribution patterns are influenced by land availability, accessibility, and existing infrastructure. The findings of this research are expected to serve as a reference for more effective regional planning and development.